Analisis Varians sebagai Alat Pengendalian Biaya Produksi pada Pabrik Tahu Ping Jaya (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine production cost control and how variance analysis is used as a means of controlling production costs at the Ping Jaya Tofu Factory. This study uses a qualitative descriptive approach. Data was collected through interviews, observations, and documentation related to production costs. Data analysis was conducted by calculating and evaluating the variance in direct raw material costs, direct labor costs, and factory overhead costs. Based on the research findings, it can be concluded that the Ping Jaya Tofu Factory has cost standards and conducts routine monitoring; however, variance analysis indicates an unfavorable variance in soybean raw material costs amounting to Rp7,800,000 due to price increases. Meanwhile, water, vinegar, and labor costs showed zero or favorable differences. Factory overhead costs such as electricity, firewood, repairs, and land rent also showed favorable differences, except for auxiliary material costs, which showed a favorable difference of Rp95,000. Internal constraints include waste management and equipment maintenance, while the dominant external constraint is soybean price fluctuations.